2006
DOI: 10.1001/archopht.124.10.1428
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor A in Eyes With Uveal Melanoma

Abstract: To determine the presence of vascular endothelial growth factor A (VEGF-A) in the aqueous humor of eyes with uveal melanoma and to identify its source. Methods: The VEGF-A concentrations were determined in aqueous humor samples obtained after enucleation from 74 eyes with untreated uveal melanoma and from 8 eyes with treated uveal melanoma. Patient survival and clinical and histopathological tumor variables were compared. In situ hybridization, Western blot analysis, and enzyme-linked immunosorbent assay were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 22 publications
3
104
0
4
Order By: Relevance
“…In contrast, it was of interest that VEGF, a potent angiogenic stimulator, was not comparatively more highly expressed (Table 2), as studies have shown raised VEGF in the aqueous and vitreous from patients with uveal melanoma. 14,23 It is expected that the aqueous and vitreous contain a myriad array of other factors not tested for in this preliminary study, and the relatively low comparative expression of VEGF in this study may suggest that the aqueous and vitreous of patients with uveal melanoma show a dramatic rise in a large number of other potentially more influential regulators. Further studies comparing the levels of regulators found in the aqueous and vitreous from a larger series of uveal melanomas, with comparison of the levels seen in patients with other ocular conditions, such as those undergoing vitrectomy and cataract surgery, will be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, it was of interest that VEGF, a potent angiogenic stimulator, was not comparatively more highly expressed (Table 2), as studies have shown raised VEGF in the aqueous and vitreous from patients with uveal melanoma. 14,23 It is expected that the aqueous and vitreous contain a myriad array of other factors not tested for in this preliminary study, and the relatively low comparative expression of VEGF in this study may suggest that the aqueous and vitreous of patients with uveal melanoma show a dramatic rise in a large number of other potentially more influential regulators. Further studies comparing the levels of regulators found in the aqueous and vitreous from a larger series of uveal melanomas, with comparison of the levels seen in patients with other ocular conditions, such as those undergoing vitrectomy and cataract surgery, will be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…In their study, Missotten et al [22 ]found significantly elevated aqueous VEGF levels in eyes with uveal melanoma irrespective of the treatment compared with controls and eyes with a retinal detachment alone. The current literature shows overall 5-year neovascular glaucoma rates of approximately 11-31% in modern proton-treated uveal melanoma patients with neovascular glaucoma, and this typically occurs in the first 3 years after treatment [23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…While the first studies on the application of drugs for treatment of radiation retinopathy are being reported [16] , using anti-angiogenesis drugs in the treatment of the primary tumour is still in the laboratory phase. It is known that uveal melanomas and uveal melanoma cell lines produce factors like VEGF and angiopoietin-1 and -2 [6,17] , which are known to stimulate vessel growth, an essential requirement for tumour enlargement. Inhibition of factors like VEGF may therefore contribute to inhibition of further tumour growth.…”
Section: Blocking Vessel Developmentmentioning
confidence: 99%